Levodopa Changes Functional Connectivity Patterns in Subregions of the Primary Motor Cortex in Patients With Parkinson’s Disease - Shen, Yang; Hu, Jun; Chen, Yong; Liu, Wan; Li, Yuqian; Yan, Lei; Xie, Chunming; Zhang, Wenbin; Yu, Miao; Liu, Weiguo (Frontiers in Neuroscience, 2020)
Background: The primary motor cortex (M1) is a critical node in Parkinson's disease (PD)-related motor circuitry, however, the functional role of M1 subregions is poorly understood. In this study, we investigated functional connectivity pattern changes in M1 subregions and relationships to improved clinical symptoms following levodopa administration. Methods: Thirty-six PD patients and thirty-seven healthy controls (HC) were enrolled. A formal levodopa challenge test was conducted in the PD group, and the UPDRS motor section (UPDRS-III) was assessed before (off state) and 1 hour after taking levodopa (on state). The PD group underwent resting-state functional magnetic resonance imaging in both off and on states, whereas the HC group was scanned once. We used the Human Brainnetome Atlas template to subdivide M1 into twelve regions of interest (ROIs). Functional connectivity (FC) was compared between PD on and off states(paired t test, voxel level P < 0.001, cluster level P < 0.05, GRF correction) and between patients and HC(two sample t test voxel-level p <0.001, cluster-level p <0.05). Correlations between ΔFC (differences in FC between PD off and on states) and clinical symptom improvements were examined. Results: There was decreased FC between the right caudal dorsolateral area 6 and the anterior cingulate gyrus (ACC), right upper limb region and left medial dorsal thalamus (mdTHA) and increased FC between the left tongue and larynx region and left medial frontal gyrus. ΔFC between the right caudal dorsolateral area 6 and ACC was positively correlated with UPDRS-III total score and rigidity (item 22) and bradykinesia (items 23–26 and 31) subscore improvements. ΔFC between the right upper limb region and left thalamus was positively correlated with left upper limb tremor (items 20c and 21b) and postural tremor (items 21b) subscore improvements. Conclusions: Our results reveal novel information regarding the underlying mechanisms in the motor circuits in the M1 and a promising way to explore the internal function of the M1 in PD patients. Notably, the M1 is a potential therapeutic target in PD, and the exploration of its subregion provides a basis and new insights for clinical intervention and precise drug treatment.